Identifying and Measuring Ill-Structured Problem Formulation and Resolution in Online Asynchronous Discussions - Elizabeth Murphy (The Canadian Network for Innovation in Education (CNIE), 2004)
Abstract: This paper reports on a study involving the development and application of an instrument to identify and measure ill-structured problem formulation and resolution (PFR) in online asynchronous discussions (OADs). The instrument was developed by first determining PFR processes relevant to ill-structured problems in professional practice. The processes were derived from a conceptual framework. Further refinement of the instrument was achieved by the addition of indicators of processes. These indicators are derived through application of the instrument to an actual discussion in which the processes are operationalized. Results of the application of the instrument indicated that participants engaged more in problem resolution than in problem formulation. The instrument can be further developed and refined through its application in other contexts by researchers or practitioners interested in the design and use of OADs.